Pengaruh Der, Roa, Pbv, Struktur Kepemilikan Institusi, dan Reputasi Underwriter terhadap Underpricing Saham yang IPO di BEI Periode Tahun 2016-2020 - Eko Agung Laksono; Lasmanah (Bandung Conference Series: Business and Management, 2022)
Abstact. This study aims to determine the effect of Debt to Equity Ratio (DER), Return On Assets (ROA), Price to Book Value (PBV), Institutional Ownership Structure and Underwriter's Reputation on Underpricing of Stocks conducting Initial Public Offering. The population in this study are companies that carry out IPOs listed on the Indonesia Stock Exchange in 2016-2020. Data analysis using multiple regression method and sample selection in this study using purposive sampling method with a total sample of 44 companies. The results showed that simultaneously Debt to Equity Ratio (DER), Return On Assets (ROA), Price to Book Value (PBV), institutional ownership and underwriter reputation had an effect on underpricing. Meanwhile, the partial test shows that the underwriter reputation partially affects underpricing, while other variables such as Debt to Equity Ratio (DER), Return On Assets (ROA), Price to Book Value (PBV) and institutional ownership structure had no partial effect on underpricing. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh Debt to Equity Ratio (DER), Return On Asset (ROA), Price to Book Value (PBV), Struktur Kepemilikan Institusi dan Reputasi Underwriter Terhadap Underpricing Saham yang melakukan Initial Public Offering. Populasi dalam penelitian ini adalah perusahaan yang melakukan IPO yang terdaftar di Bursa Efek Indonesia pada tahun 2016-2020. Analisis data menggunakan metode regeresi berganda dan pemilihan sampel dalam penelitian ini menggunakan metode purposive sampling dengan jumlah sempel sebanyak 44 perusahaan. Hasil penelitian menunjukan bahwa secara simultan Debt to Equity Ratio (DER), Return On Asset (ROA), Price to Book Value (PBV), kepemilikan institusi dan reputasi underwriter berpengaruh terhadap underpricing. Sementara untuk pengujian secara parsial menunjukanbahwa reputasi underwriter secara parsial berpengaruh terhadap underpricing, sedangkan variabel lainnya seperti Debt to Equity Ratio (DER), Return On Asset (ROA), Price to Book Value (PBV) dan struktur kepemilikan Institusi tidak berpengaruh secara parsial terhadap underpricing.